Protein-film-mediated strategies for the electrochemical immunosensing of circulating biomarkers - Fleschhut, FM (2024)
The electrochemical quantification of protein biomarkers from complex samples such as human serum promises vast potential for the solution of future healthcare challenges. Chapter 1 will summarise the current state-of-the art and show that such assays can typically be categorized as either sandwich-type or label-free. Label-free methodologies directly transduce a single interfacial recognition event and therefore demand specially designed electrode modifications that come with challenges in stability. While sandwich methodologies offer high sensitivity, they are associated with considerably higher assay complexity as well as time and cost requirements. This work aims to expand the currently available range of methodologies by introducing three distinct approaches focusing on facile implementation as well as simple and stable sensing platforms. Chapter 3 will introduce the first example of an amperometric dot blot assay for the detection of target protein from diluted serum. The proposed method dismisses any electrode functionalisation and aims to solve practical challenges regarding storage, transport and handling while catering clinical demands for the target proteins. Chapter 4 aims to explore the use of ensemble redox labelling for the electrochemical quantification of target protein. Hereby, the non-specific redox tagging of all protein in serum in combination with antibody-mediated target recognition at an electrode surface is used to yield a voltametric assay offering facile and multiplexable sensing. Chapter 5, finally, elucidates the use of the electroactive protein Azurin as a transducing and anti-fouling building block for the formation of stable biosensory surfaces for target protein immunosensing based on redox-capacitance. A summary of results and an outlook for future work is provided in Chapter 6. All experimental details are summarised in Chapter 2. Supportive information is provided in the appendix (Chapter 7). All referenced work is listed in Chapter 8.